(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Islamic pawn-broking (Ar-Rahnu) activities in Malaysia began in 1990s. Currently, there are various categories of institutions offering Islamic pawn-broking services, ranging from financial and non-financial institutions such as cooperatives, companies and state-linked companies. Each category of institutions is governed by a different regulatory body. The diversity of governance in ar-rahnu activities creates difficulty in coordination and enforcement of these activities. In order to standardize the governance of Ar-Rahnu, there was a suggestion to appoint a single regulatory body for Ar-Rahnu. Hence, the purpose of this paper is to discuss the appropriate agency to be appointed as the regulatory body for Ar-Rahnu activities in Malaysia. In addition, focus will also be given to see how some of the functions of existing institutions can be utilized for the purpose of strengthening the governance mechanisms of Ar-Rahnu in Malaysia. This is a qualitative study with multiple case studies approach, for which data was collected through analysis of documents and interviews to obtain the results. The study finds that determination of power to regulate the activities of Ar-Rahnu in Malaysia should be with reference to the Federal Constitution of Malaysia, and the Ministry of Finance, Malaysia, is the most suitable body to streamsline ar-Rahnu activities, with the aid of Bank Negara Malaysia (BNM), the Companis Commission of Malaysia (SSM), the Malaysian Co-Operative Societies Commission (SKM), and the State Religious Councils (MAIN). Keywords: Ar-Rahnu, jurisdictions, supervision, law